Abstract ID: 157 Development of Geant4-based patient-specific QA system of gamma knife treatment plans using automated DICOM-RT interface. (October 2017) - Choi, Hyun Joon; Sohn, Jason W.; Chung, Hyun-Tai; Kim, Tae Hoon; Min, Chul Hee
Abstract : Gamma knife system which uses 192 small photon beams is widely considered as a very precise modality for intracranial radiosurgery. However, there are still limitations in current treatment planning system (TPS) for accurately estimating the absolute dose in the small volume, or the dose distribution in the inhomogeneous area such as the case of embolization of arteriovenous malformations and the located target volume behind an air cavity[1] . The purpose of this study is to develop quality assurance (QA) system of gamma knife treatment plans based on a patient-specific model constructed by an automated DICOM-RT interface in Geant4. The Leksell Gamma Knife Perfexion was designed in Geant4.10.00 based on the manufacturer's detailed information. Dose distributions in the spherical water phantom with a diameter of 16 cm were compared between Geant4 and the film measurement for the validation system. For extracting the patient-dependent parameters, automated DICOM-RT interface was developed for constructing the patient-specific model. In-house developed system is able to manually define the physical property of a special volume using the region of interest (ROI) contour data stored in a DICOM file. The dose distributions in the water phantom were compared between Geant4, measurement data and manufacture's values in terms of full width at half maximum (FWHM). FWHM of Geant4 and measurement were quite well matched with manufacture's value within 0.3, 0.2 and 0.7 mm in both the x and y direction for 4, 8 and 16 mm, respectively. Furthermore, the dose distributions of Geant4 and commercial TPS were well matched for different beam size combinations for each of the eight sectors. The developed QA system shows the potential to precisely estimate the dose distribution in the patients. In the future, assessment of the absolute dose distribution calculated by Geant4 and commercial TPS for the clinical cases will be performed. Moreover, magnetic resonance (MR) images will be employed in our system for sophisticated modelling the heterogeneities in the patients.